A comparative anatomical study of the genus Puschkinia Adams in Turkey - Yetişen, Kadriye (Array, 2020)
In the study, Puschkinia scilloides Adams, P. bilgineri Yıldırım, and P. peshmenii Rix et B. Mathew were compared anatomically. Although the stem vascular bundles were arranged in two rows in P. peshmenii, they can observed in three rows in P. scilloides and P. bilgineri. In addition, some differences were found, such as the metaxylem number in the root, number of vascular bundles in the scape, presence of raphide crystals, and number of protruding epidermis cells at the tip of the leaf. These differences have been found to be taxonomically useful for distinguishing these species. Moreover, similarities and differences between Puschkinia Adams and the taxonomically closely related Scilla L. section Chionodoxa Boiss. and Scilla bifolia L. taxa were also discussed.